Does Alicante Have the Longest Urban Geometric Illusion in the World?. (December 2013) - Taylor, Steve; Taylor, Matthew
Interest in geometric illusions in architectural design was restimulated in the 1970s by the publication of a paper by Gregory and Heard on the Café Wall illusion. Illusory patterns have been used in urban design for centuries. This brief note identifies two further examples of urban illusions found in Alicante, Spain and suggests that they may represent currently the longest examples of urban geometric illusion in the world.